Construction and Usage of Control Charts for Some Properties of Sugar Crystals - Hassan, Alla Abdalrhman Amer; Abusabah1, Elnour Kamaledin (Gezira Journal of Engineering and Applied Sciences, 2018)
Statistical process control benefits organization by providing a systemic method for monitoring and evaluation of process variation. In this research application of statistical process control using variables control charts on the data from Al Gunaid Sugar Factory season (2015 – 2016) to test quality for three properties of sugar crystal namely purity%, colour(IU) and moisture%. The samples were selected at systemic randomness  to cover all the season days. The periodic interval of sample was about 2 hours, the sample size is equal 10 and the subgroups are equal 15. Two variables control charts were constructed ( - charts and R - - charts) for the purity%, colour (IU) and moisture % of sugar crystals. Six random samples were taken and measured  for the purity%, colour and moisture and plotted on the constructed charts. The average of purity% was  98.03% . The  charts for purity of sugar crystal showed that, Three points were located below lower action limit and one point was located above upper action limits other points were located within the stable limits.  This means that process was out of control  The average of colour was  342.24 (IU). The  -chart for colour of sugar showed that  three  points were located above upper action limit and three points were located  above upper  warning limits.  This means that the process was out of control and therefore the cause for that should be searched for.  The average of moisture  was 0.0572 %.  – chart for moisture showed that one point was located above upper warning limit, other points were located between the upper and lower warning limits  this indicated the process was under control. The study recommended  to construct control charts for other properties of sugar crystal such as Ash% , and Brix% .